Fatigue Life of Construction Elements in a Complex Stress State. (1st July 2014) - Łukaszewicz, Krzysztof
Abstract : This paper presents a method of assessing fatigue strength for a body in conditions of cyclical tension and torsion. The theoretical calculations have been conducted using the criterion of averaged structural microdamage resulting from local slips. The description of microdamages of such a body, in the view of the slip concept, was done by using a half-sphere with a unit radius, on the surface of which the location of all local physical planes and slip systems was determined employing three angles. A computer method was used to determine the slip boundaries in a complex stress state, analyzing the slip condition for all combinations of angles. Based on the calculated values of the microdamages' intensity function, the number of loading cycles until the moment of fracture initiation was estimated. Experimental verification of the suggested criterion was conducted using cylindrical smooth specimens, made of C45 steel. The tests of fatigue strength were made under conditions of a constant amplitude of zero-start pulsating loads.